Pengolahan Limbah Cair Industri Kain Jumputan Untuk Menurunkan Zat Warna Dengan Menggunakan MembranPolysulfonSecara Ultrafiltrasin : PENGOLAHAN LIMBAH CAIR INDUSTRI KAIN JUMPUTAN UNTUK MENURUNKAN ZAT WARNA DENGAN MENGGUNAKAN MEMBRAN POLYSULFON SECARA ULTRAFILTRASI - Putri Chairani Putri Chairani; Selastia Yuliati; Jaksen (Politeknik Negeri Sriwijaya, 2022)
Palembang Jumputan Fabric, or commonly called Rainbow Fabric, one of the crafts produced with the jumputan technique, (Tie and Dye) is a technique of dyeing fabric by dipping it in colored ink, by adding silk and satin materials with a natural mixture of coloring method of natural and chemical origins. There have been many studies regarding the treatment of jumputan fabric wastewater using adsorbents, but this method has a weakness. Similarly, it allows the adsorbent to be left behind in the jumputan fabric wastewater. The purpose of this research is to treat the liquid waste of jumputan fabric with polysulfone membrane to reduce dry stuff . The membrane will be made using DMAc solvent and a PEG 400 additive with a composition of 18% polysulfone; 62% Dmac; and 20% PEG. The liquid waste of jumputan cloth will be purified with polysulfone membrane by ultrafiltration. In this study, the liquid waste of jumputan fabrics with variations of PAC Coagulants 500 ppm, 1000 ppm, and 1500 ppm was used, as well as with pressure variations of 0.5, ; 1; 1.5 , and 2 bars. From the results of the study, it was found that the rejection of the dye was 23.69%. Keywords: Liquid Waste, Polysulfone, Ultrafiltration